Peran Orang Tua dalam Mendampingi Generasi Z - Merensiana Hale (Institut Agama Kristen Negeri Kupang, 2022)
Generation Z with its uniqueness is often a challenge for parents (Millennial generation) in accompanying them. Generation Z is in transition and the digital context that is abundant in information and communication media often makes them carried away by negative currents. Therefore, parental assistance is needed that can be used as a reference. This paper aims to help generation Z parents by offering the attitudes of Z generation parents in accompanying their children. This paper uses a relevant literature study research method. The results of this study are to offer the attitudes of parents in accompanying children, namely: loving children, understanding and knowing children, being present, discernment, speaking, being an example, giving freedom to choose, giving praise, liberating, willing to accompany in a life of faith. In an effort to educate Generation Z, parents can apply several mentoring attitudes. The recommendation of this paper is the attitude of parents in assisting the Alpha generation.